Insights into maternal and neonatal anti-Ro/SSA antibodies: implications on pregnancy and neonatal health - Al Emadi, Samar; Satti, Eman; Hadwan, Nawal (Frontiers in Lupus, 2024)
Introduction The presence of anti-Ro/SSA antibodies is associated with an increased risk of adverse maternal and neonatal outcomes in patients with autoimmune rheumatic diseases. We evaluated the rate of adverse maternal and neonatal outcomes in a cohort of pregnant women with positive anti-Ro/SSA antibodies in Qatar and explored the significance of neonatal anti-Ro/SSA antibodies. Methods This retrospective observational study was conducted at the largest tertiary institute in Qatar between July 2016 and January 2021. The study included pregnant women with confirmed anti- Ro/SSA positivity who were consistently followed to evaluate maternal and fetal complications. Results One-hundred-thirty-two pregnancies from 79 women were included in the analysis. Anti-Ro/SSA positivity was observed in all pregnancies, whereas anti-LA/SSB positivity only in 23.5% of pregnancies. Of the 132 pregnancies, 99 (75%), 27 (20%), and 6 (4.6%) resulted in live birth, miscarriage, and intrauterine fetal demise (IUFD), respectively. Among the 99 live births, serology testing for anti-Ro/SSA was performed on 84 neonates, of which only 45 were positive. Neonates born to mothers with primary SS and rheumatoid arthritis (RA) had higher median antibody titers (240 IU/ml) than those born to mothers with systemic lupus erythematosus (SLE) (89.5 IU/ml)). The rheumatic diseases (SS, RA, or SLE) showed no significant correlation with adverse pregnancy and fetal outcomes. Congenital heart block (CHB) was recorded in only two infants (2%), and one infant had neonatal lupus (1%). Interestingly, CHB was only observed in previously asymptomatic women who were subsequently diagnosed with SS. Most women (85.9%) were treated with hydroxychloroquine throughout pregnancy. These women had lower rates of miscarriage and neither of their infants presented with CHB. Conclusion Miscarriage is the most common adverse outcome reported in this cohort. The incidence of CHB was among asymptomatic carriers only. Nevertheless, hydroxychloroquine use seems to lower the vulnerability to these adverse events. However, these findings need to be validated in larger controlled cohorts. This study is one of few to report results on neonatal anti-Ro/SSA antibody testing.